Against equality of opportunity - Cavanagh, Matt (Clarendon Press, 2002)
These days almost everyone seems to think it obvious that equality of opportunity is at least part of what constitutes a fair society. At the same time they are so vague about what equality of opportunity actually amounts to that it can begin to look like an empty term, a convenient shorthand for the way jobs (or for that matter university places, or positions of power, or merely places on the local sports team) should be allocated, whatever that happens to be